PENGEMBANGAN E-LKPD BERBASIS CREATIVE PROBLEM SOLVING BERBANTUAN LIVEWORKSHEETS MATERI PERUBAHAN WUJUD BENDA UNTUK MENINGKATKAN KREATIVITAS SISWA - Tarisa Rawanda; Lukman Hakim; Lefudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop E-LKPD based on creative problem solving assisted by liveworksheets of material changes in the form of objects to increase student creativity that is valid, practical and effective. This research is a type of Research and Development (R&D) research. This research uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection techniques used were questionnaires, tests, and documentation. Data analysis techniques consist of validity analysis, practicality analysis, and effectiveness analysis. The validity analysis conducted by three experts, namely material experts, media experts, and linguists with an average score of 94.8% of the category was very valid. The analysis of practicality in students through the individual trial stage and the small group trial stage obtained an average score of 90.7% of the very valid category. The analysis of effectiveness to students in one class consisting of 36 people as a large group obtained an average N Gain score of 0.76 in the category was very effective. Therefore, it can be concluded that the development of E-LKPD based on creative problem solving assisted by liveworksheets is declared valid, practical, and effective in helping the learning process. Keywords: Change in the form of object, Creative Problem Solving, Creativity, E-LKPD, Liveworksheets